The Effect of Promotion on Purchase Decision at Cafe Praja Bintaro, South Tangerang - Setiawan, Christin; Octarina, Dian; Pangosta, Jeefrey Rabito (Institut Pariwisata Trisakti, 2022)
This study aims to determine the effect of promotion on purchasing decisions. This research is a quantitative descriptive study with a simple regression analysis method. The sampling technique used is accidental sampling. Consumers who happen to meet with researchers can be used as samples and are feasible as data sources. The population in this study were all consumers of Café Praja Bintaro, South Tangerang, a sample of 100 respondents. The results showed that promotion had a significant effect on purchasing decisions. Promotions are carried out offline and can also be done online, such as doing promotions on Instagram, Facebook, and Twitter. Promotion is carried out by the company and employees and can also be done by consumers; Therefore, Café Praja Bintaro South Tangerang is always expected to maintain product quality and service quality. Keywords: Promotion, Purchase Decision